Article RETRACTED due to manipulation by the authors Supporters of football and social movements: An examination of resource mobilization among fans of the PSM club in South Sulawesi - Hasyim Hasyim; Abdul Hakim Siregar; Hasanudin Kasim; Idris Moh Latar; Putra Sastaman B; Ramli Ramli; Mikkey Anggara Suganda; Didi Suryadi; M. Rachmat Kasmad; Ardo Okilanda (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Supporters in a football game are one of the encouraging factors for playing in a match. Having active and enthusiastic supporters can help build a positive atmosphere around the club. Research on social movements through the mobilization of resources of PSM club supporters in South Sulawesi to win the league can discuss two main dimensions: support for the football team and support for social movements. PSM club supporters can mobilize human resources by providing moral support, following and supporting the team in every match. This research uses qualitative research through in-depth interviews and analyzing data using grounded theory analysis techniques. The technique for taking informants uses purposive sampling. The informants in this research were 30 respondents. Our findings show that the victory of active and enthusiastic supporters can help build a positive atmosphere around the PSM Makassar club in the 2022/2023 League 1 competition, there is the formation of a social movement of supporters. Active and enthusiastic supporters can help build a positive atmosphere around the PSM Makassar club in South Sulawesi is massive because they can take forms and instruments to achieve goals by showing high commitment in supporting PSM Makassar through resource movements which can result in effective mobilization of supporting resources.